Moderating and mediating effects of switching costs on the relationship between service value, customer satisfaction and customer loyalty: investigation of retail banking in Vietnam - Vu Minh Ngo; Drahomíra Pavelková (Journal of International Studies)
Switching cost highlights the way how companies create barriers to proactively prevent customer defection which directly and significantly affects customer loyalty and then companies’ performance. The purpose of this paper is to provide empirical evidences about the impact of switching cost on customer loyalty by examining its mediating and moderating effects on the relationships between service value, customer satisfaction and customer loyalty. Specially, two difference types of switching costs, positive one and negative one, are proposed and tested independently in order to provide more insights about their impacts. The data about switching costs and other constructs are collected from 261 retail banking customers, and analysed using structural equation modelling and moderated path analysis. It is found that positive switching costs increase customer loyalty by partly transforming the effect of service value and customer satisfaction into customer loyalty. While negative switching cost only mediates the service value-loyalty relationship. Moreover, only negative switching cost has significant moderating effect on the satisfaction-loyalty relationships. Finally, the analysis reveals that negative switching cost might also weaken good impacts from positive switching cost on satisfaction-loyalty relationships.